A Comparative Effects of Episodic Tension-type Headache Treatment between Royal Thai Massage with Thai Massage: Preliminary study - Inphrom, Pitchayapha; Kumkhainam, Pohntip; Khotchasan, Jirawadee; Manmai , Panuphong; Tunchai, Gusumas (Health Science Journal of Thailand, 2025)
The quasi-experimental research aimed to study the comparative effects of episodic tension-type headache treatment between Royal Thai massage and Thai massage, conducted on 30 female students in Bansomdejchaopraya Rajabhat University. Fifteen of them received Royal Thai massage, and the other fifteen received Thai massage for 30 minutes per week for three weeks. Their stress levels were assessed based on the assessment form made by the Department of Mental Health (ST-5), which divided the muscle pain levels into 10 categories. The muscle tenderness was assessed using an algometer, and the range of motions of the cervical spine was assessed using a goniometer before and after the treatment, respectively, with the statistical significance of 0.05. The results revealed that both Royal Thai massage and Thai massage could help alleviate pain and stress and enhance the pressure – pain threshold and the movement of the cervical spine with the statistical significance of 0.05 However, no difference was observed between the two groups. It is apparent that both Royal Thai massage and Thai massage can yield equivalent results of alleviating episodic tension-type headache. Therefore, this knowledge could be adopted in association with massage therapy that integrates both Royal Thai massage and Thai massage in patients with episodic tension-type headache.